2016
DOI: 10.1071/rd14345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic identification and expression profiling of a novel β-defensin gene cluster in the equine reproductive tract

Abstract: 25 β-defensins are small cationic proteins with potent immunoregulatory and antimicrobial 26 activity. The numbers of genes encoding these peptides vary significantly between and within 27 species but have not been extensively characterised in the horse. Here, we describe a 28 systematic search of the Equus caballus genome which has identified a cluster of novel β-29 defensin genes on chromosome 22, which is homologous to a cluster on bovine chromosome 30 13. Close genomic matches were found for orthologs of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
2
14
0
2
Order By: Relevance
“…This is in agreement with the work by Tollner et al (2011), who demonstrated that spermatozoa from men with mutations in DEFB126 have lower lectin binding, which is associated with fewer O-linked oligosaccharides, an altered ability to penetrate synthetic mucus and reduced fertility. Indeed, beta-defensins are conserved across mammalian species and are expressed within both male and female reproductive tissues as demonstrated by our group for equine (Johnson et al 2016), bovine (Narciandi et al 2011(Narciandi et al , 2014 and ovine (Hall et al 2017) subjects. The addition of sialic acid moieties to defensin peptides confers a negative charge to spermatozoa, thereby repelling the negatively charged mucus and facilitating migration of non-capacitated spermatozoa through electronegative mucus (Tecle & Gagneux 2015).…”
Section: Gene/breedmentioning
confidence: 66%
“…This is in agreement with the work by Tollner et al (2011), who demonstrated that spermatozoa from men with mutations in DEFB126 have lower lectin binding, which is associated with fewer O-linked oligosaccharides, an altered ability to penetrate synthetic mucus and reduced fertility. Indeed, beta-defensins are conserved across mammalian species and are expressed within both male and female reproductive tissues as demonstrated by our group for equine (Johnson et al 2016), bovine (Narciandi et al 2011(Narciandi et al , 2014 and ovine (Hall et al 2017) subjects. The addition of sialic acid moieties to defensin peptides confers a negative charge to spermatozoa, thereby repelling the negatively charged mucus and facilitating migration of non-capacitated spermatozoa through electronegative mucus (Tecle & Gagneux 2015).…”
Section: Gene/breedmentioning
confidence: 66%
“…Our group has recently discovered and profiled the expression of a cluster of 19 (cattle) and 13 (horses) novel β-defensin genes along the male and female reproductive tracts [ 26 , 27 ]. Studies in cattle have shown that these genes are preferentially expressed in the reproductive tract [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spermatozoa from men with DEFB126 mutations have lower lectin-binding which is associated with fewer O-linked oligosaccharides, altered ability to penetrate synthetic mucus and reduced fertility (Tollner et al 2011). Beta-defensins are conserved across mammalian species and are expressed within both male and female reproductive tissues (Equine; Narciandi et al 2011, Johnson et al 2015, Ovine, Hall et al 2017. In cattle, DEFB126 is preferentially expressed in the caudal epididymis (Narciandi et al 2016) with similar binding patterns on the sperm surface to macaque (Fernandez-Fuertes et al 2016) and increases sperm motility and mucus penetration (Fernandez-Fuertes et al 2016) as well as sperm binding to oviductal epithelial explants in vitro (Lyons et al 2018).…”
Section: Cervical Mucus Proteomementioning
confidence: 99%